Association Between Malnutr ition & Colostrum For Severe Pneumonia - Faiza Siddiqui; Mohammad Iqbal; Kausar Aamir; Zareen Naz (ziauddin University, 2022)
Background: Pneumonia remains one of the main causes of childhood mortality despite the availability of simple, safe, effective and inexpensive interventions to curb its mortality. This could result from sub-optimal care seeking practices and child rearing, supplemented by lack of access to healthcare.We conducted a studyto identify the association of malnutrition and initiation of breastfeeding variables with severe pneumonia and pneumonia/no pneumonia Objective: To determine association of malnutrition and colostrums intake among children aged 2-24 months admitted in tertiary care hospital for severe pneumonia. Methods: A total of 288 patients with severe pneumonia were included in this case-control study. Patients were divided into 2 groups with 144 patients in each group selected through non-probability consecutive sampling. Sample size was calculated using WHO sample size calculator keeping power of test at 80%, P1= 1% and P2=7.8%. Data was analyzed through SPSS version 19 and p-value < 0.05 considered as significant. Association between study variables and severe pneumonia was computed using Chi Square Test. Results: Mean age for group A (67 males and 77 females) was 13.00±6.40 months and group B (78 males, 66 females) 12.83±6.90 months. Malnutrition was seen in 41% of group A and 17.4% of group B patients. Colostrum intake (Initiation of breast feeding with 72 hours) was reported in 78.5% of group A and 79.2% of group B. There was a significant association of malnutrition with severe pneumonia (p=0.000) whereas, no significant relation was found with colostrum intake (p=0.885). Conclusion: Malnutrition was significantly associated with severe pneumonia. Colostrum was the most prevalent factor in both groups but the difference was insignificant.